Study of Association between Lipid Profile and Thyroid Hormones in Pregnancy - Ibrahem, Suhad abdulaziz; Ahmed, Salman A (Al-Nahrain Journal of Science, 2018)
Thyroid function during pregnancy is important for both the mother and the developing fetus. Especially during the first trimester, when the fetus is completely dependent on the mother for thyroid hormone. Increase liver metabolism is seen, renal plasma flow increases during pregnancy. This Study includes measurement of the thyroid hormones T3,T4,TSH and lipid profile, in serum of fifty pregnant women between 16-50 years during the three trimesters compared with serum of twenty non-pregnant women between 17-45 years. Results of pregnant women at first trimester showed that there was a significant difference at (P<0.001) in hormones T4, in the second trimester it was found that a highly significant difference at (P<0.001) in hormones T3, T4 and TSH at (P<0.05), and In the third trimester there was a highly significant difference at (P<0.001) in hormones T4 and T3 (P<0.05) all compared with the control group. The results of lipid profile showed that at the second trimester there was a significant difference at (P<0.05) in cholesterol and LDL, in the third trimester it was found a highly significant differences at (P<0.001) in cholesterol, triglyceride, LDL and VLDL compared with the control group. A strong positive correlation coefficient was found at the firsttrimister between T3 with a weak of gestation and HDL. and between TSH with cholesterol, VLDL, triglyceride, LDL, CHO/HDL and LDL/HDL, at the second trimester a significant positive correlation coefficient was found between T3 with triglyceride, VLDL and CHO/HDL. And there was a negative correlation coefficient between TSH with triglyceride, VLDL and T3. At third trimester there was a negative correlation coefficient between T4 with triglyceride and VLDL. Results of non-pregnant group were found with a negative correlation coefficient between T3 with triglyceride, VLDL, LDL, and LDL/HDL and there was a positive correlation coefficient between TSH with HDL, and T3.